Radar observations of a thunderstorm - MITRA, H. (MAUSAM, 1955)
The paper describes the results of a study of a winter thunderstorm which occurred at New Delhi between 2150 IST of the 14th and 0030 1ST of 15 January 1953 due to the passage of a western disturbance. The radar echoes as seen on the scope of a 3-cm'AN/APQ-13 set have been explained with the help of the available surface and upper air data. The mechanism of formation and decay of the main thunder storm cell and its associated secondaries have been described with the help of radar photographs taken at short intervals.